Moral Economy at Work Ethnographic Investigations in Eurasia - Yalçın-Heckmann, Lale (Berghahn Books, 2021)
The idea of a moral economy has been explored and assessed in numerous disciplines. The anthropological studies in this volume provide a new perspective to this idea by showing how the relations of workers, employees and employers, and of firms, families and households are interwoven with local notions of moralities. From concepts of individual autonomy, kinship obligations, to ways of expressing mutuality or creativity, moral values exert an unrealized influence, and these often produce more consent than resistance or outrage.